The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1111/j.1747-4477.2002.tb00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Vital Pulp Therapy In Cariously Exposed Permanent Teeth And Its Limitations

Abstract: Vital pulp therapy for cariously exposed permanent teeth remains one of the most controversial areas in dentistry. Because a vital, functioning pulp is capable of initiating several defence mechanisms to protect the body from bacterial invasion, it is beneficial to preserve the vitality and health of an exposed pulp rather than replace it with a root filling material following pulp exposure. There is no consensus on the survival rate of formerly cariously exposed pulps. Observation time, judgement criteria, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 52 publications
1
88
0
Order By: Relevance
“…The pulp capping materials should also provide good sealing ability 3,4) . The major problems with vital pulp therapy are the unpredictable severity of the inflammatory condition of the underlying tissue and variable long-term clinical success 5,6) . Chronic inflammation in dental pulp tissue may lead ultimately to degenerative pulp response or pulp necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The pulp capping materials should also provide good sealing ability 3,4) . The major problems with vital pulp therapy are the unpredictable severity of the inflammatory condition of the underlying tissue and variable long-term clinical success 5,6) . Chronic inflammation in dental pulp tissue may lead ultimately to degenerative pulp response or pulp necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in cases where MTA is used, the dentine bridge has been shown to be thicker and more regular, the rate of bridge formation is greater and as the impermeability is very good, the underlying tissues are better protected with less inflammation and hyperemia [20]. Following amputations made with MTA, it has been reported that colouring in the teeth may be seen [21]. Therefore, the use of white-coloured MTA is recommended [22].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, failure to protect the pulp can lead to infection caused by remaining bacteria. In any case, the vitality of the dental pulp of an aged person appears to be weaker than that of a young person [28]. Discussing about caries, it is important to note that just in the 1870's, a foot-powered drill and a fully adjustable chair were created by an innovator called James Beall Morrison in order to treat caries more effectively [29].…”
Section: Findings and Discussion Of Mr Lloyd's Reportmentioning
confidence: 99%